A Retrospective Study on the Mortality Rate of Camel Calves, Leading Causes, and Associated Risk Factors in Borana Zone, Oromia Regional State, Ethiopia - Abduljami, Gerade; Kumbe, Adem (Universitas Airlangga, 2024)
Background: Camelus dromedarius (one-humped camel) is an important livestock species uniquely adapted to arid and hot environments. Purpose: This study aims to determine the mortality rate of camel calves and to investigate the potential risk factors associated with it. Methods: Retrospective data were collected through interviews with livestock owners using a semi-structured questionnaire from February 2020 to January 2021. During the study period, a total of 1,249 calves were born. This allowed for assessment of annual mortality rate and its main contributing factors. Results: The average annual mortality rate was 26% (1.29 ±1.77), while the overall mortality rate was 55% (1.30 ± 1.85). Malnutrition (5%), unexplained causes (6%), and diseases (24%) were the three leading causes of calf mortality. Diarrhea (57%), nonspecific diseases (45.4%), respiratory diseases (23%) were significant among the diseases. Mistakes in the management of young livestock included limiting access to colostrum and milk for human consumption, as well as poor care and health management. Conclusion: The results of this study suggested that the pastoral livestock production system used in Borena has a serious problem with calf mortality. The first month of life had the highest mortality rate of 26%. Diseases, starvation, and unexplained causes were the leading causes of calf mortality. In addition, calf mortality was associated with the timing of birth and colostrum feeding.